Case report: Clinical manifestations and genotype analysis of a child with PTPN11 and SEC24D mutations - Miao, Yuqi; Chen, Jiahui; Guo, Xiaoya; Wei, Yu; Wu, Xiaozhi; Sang, Yanmei; Wu, Di (Frontiers in Pediatrics, 2022)
Background: The PTPN11 gene, located at 12q24.13, encodes protein tyrosine phosphatase 2C. Mutations in the PTPN11 gene can lead to various phenotypes, including Noonan syndrome and LEOPARD syndrome. The SEC24D gene is located at 4q26 and encodes a component of the COPII complex, and is closely related to endoplasmic reticulum protein transport. Mutations in SEC24D can lead to Cole-Carpenter syndrome-2. To date, dual mutations in these two genes have not been reported in the literature. Methods: We report a patient with short stature and osteogenesis imperfecta as the primary clinical manifestation. Other clinical features were peculiar facial features, deafness, and a history of recurrent fractures. Whole exome sequencing was performed on this patient. Results: After whole-exome sequencing, three mutations in two genes were identified that induced protein alterations associated with the patient's phenotype. One was a de novo variant c.1403C>T (p.Thr468Met) on exon 12 of the PTPN11 gene, and the other was a compound heterozygous mutation in the SEC24D gene, a novel variant c.2609_2610delGA (p.Arg870Thrfs*10) on exon 20 and a reported variant c.938G>A (p.Arg313His) on exon 8. Conclusions: Concurrent mutations in PTPN11 and SEC24D induced a phenotype that was significantly different from individual mutations in either PTPN11 or SEC24D gene. Personalized genetic analysis and interpretation could help us understand the patient’s etiology and hence develop treatments and improve the prognosis of these patients.